Oxidative and inflammatory status, daily weight gain, intake and feed efficiency on natural congenitally Neospora caninum infected dairy calves - Miqueo, Evangelina; Cruz, Micaela Solange; Moore, Prando Dadin; Campero, Lucia Maria (Elsevier, 2025)
This study explored the effect of Neospora caninum infection on oxidative and inflammatory status in newborn dairy calves and the relationship between antibody levels in dairy cows and congenital transmission. The study involved 59 cow-calf pairs from a dairy herd in Mar y Sierras Basin, Argentina. Calf performance metrics (total intake, daily weight gain, feed efficiency, and fecal consistency) were recorded. Serum samples from cows were collected prepartum, and from calves at birth (pre-colostrum), 7, 14, and 63 days of birth to assess N. caninum antibodies and oxidative status. No differences in total intake, daily weight gain, feed efficiency, or fecal score were observed between N. caninum infected and non-infected calves. Similarly, total antioxidant status, thiobarbituric acid reactive substances, and haptoglobin levels did not differ between groups. Among the 59 cows evaluated, 17 tested seropositive for N. caninum. Of these, 15 gave birth to N. caninum seropositive calves, corresponding to a vertical transmission rate of 88.2 %. Among these cows, higher relative index percentage (RIPC) values were associated with successful vertical transmission (mean RIPC 69.8 vs. 7.8; p = 0.01). Congenitally infected calves also had higher RIPC values compared to those that seroconverted postnatally (mean RIPC 32 vs 17.4; p = 0.02). The absence of oxidative stress differences suggests parasite adaptation in congenitally infected calves without clinical signs. This study highlights a substantial transplacental transmission linked to higher RICP in seropositive cows and limited exposure to N. caninum during the artificial rearing. Results emphasize two factors: higher antibody levels correlated with congenital transmission and the absence of horizontal transmission during dairy calf rearing.